Ambiguity and Vagueness in Legal Language - Kadhim, Murtada Jabbar (Al-Adab Journal, 2023)
This paper investigates the phenomena of vagueness and ambiguity in legal language starting from the conceptions of legislators who do not distinguish between them in interpreting legislative texts. We will start from this problem to show that there is a difference between vagueness and ambiguity as they differ in terms of conception. We will make clear that legal language is like ordinary language in that it is subject to vagueness and ambiguity although the jurists have put a set of rules and criteria which one resorts to in interpreting and explaining the text.